TOWARD: a metabolic health intervention that improves food addiction and binge eating symptoms - Saner, Erin; Kalayjian, Tro; Buchanan, Laura; Calkins, Matthew; Soto-Mota, Adrian; Jun, Daekwang; Sethi, Shebani (Frontiers in Psychiatry, 2025)
Food Addiction is an increasingly relevant clinical and public health issue given its impact on metabolic health, mental health, and quality of life. Therapeutic carbohydrate reduction (TCR) has been shown to improve the symptoms of food addiction as measured by the modified Yale Food Addiction Scale (mYFAS) 2.0. We discuss a novel telemedicine intervention, in an employee wellness setting, utilizing TOWARD principles: Text-based communications, Online interactions, Wellness coaching, Asynchronous education and community support, Real-time biofeedback and remote monitoring, and Dietary modification with an emphasis on TCR to treat symptoms of food addiction and binge eating. Food addiction symptoms decreased by 40.7% and binge eating symptoms decreased by 34.7%. In an employee wellness setting, we observe a metabolic health intervention can improve weight, lower financial cost through medication deprescription, and improve mental health symptoms related to food.